From “a great counter attraction to the ale-house and low music hall” to “the one place everybody goes”: the public library in The Globe and Mail, 1860-2016. - Beraldo, Sofia; Coubry-Forte, Chelsea; Desjardins, Katrina; Isings, Erin; McCandless, Kate; McKenzie, Pam (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2021)
Canadian public libraries espouse a set of values that may not be congruent (e.g., preserving “high” culture vs providing access to inclusive collections). Tension or conflict can result when stakeholders emphasize different values, so it is crucial to attend to values in stakeholder accounts, including those in the mass media. This poster presents a) emerging findings from a study of the representation of public libraries in The Globe and Mail since 1860; and b) reflections on the research and research communication process as an innovative experiential learning opportunity for the interdisciplinary team of faculty, graduate, and undergraduate students.